Nonsurgical Reshaping of the Lower Jaw With Hyaluronic Acid Fillers: A Retrospective Case Series - Rauso, Raffaele; Rugge, Luigi; Chirico, Fabrizio; Nicoletti, Giovanni Francesco; Fragola, Romolo; Bove, Pierfrancesco; Zerbinati, Nicola; Lo Giudice, Giorgio (Dermatology Practical & Conceptual, 2022)
Introduction: Non-surgical aesthetic treatments of the lower face are increasingly in demand, particularly aimed to restore facial youth following the changes secondary to a progressive resorption of facial skeleton and atrophy of facial fat compartments, which give the perception of a descent face. Objective: The aim of this research is to describe non-surgical reshaping of aged lower jaw by means of hyaluronic acid fillers. Methods: A retrospective analysis of data from adult female patients undergoing treatment of the lower third of the face with hyaluronic acid injections was performed. Injection techniques, relevant anatomy of the anatomical area and rheological properties of the fillers to be used are highlighted. Results: Thirty-six consecutive patients were enrolled (100% female; mean age, 45.7 years). A minimum of 4 vials, up to 7, of hyaluronic acid filler, were injected in order to achieve the desired results. Visual analog scale (VAS) was used to assess patient satisfaction. Thirty-two patients (88.8%) rated their appearance post-treatment with a satisfaction score ranging between 85 and 100%. Total absence of ecchymosis and/or swelling in the early post-operative days has been highlighted. There were no cases of infection, paresthesia, hematoma or necrosis. Conclusions: Jaw line remodeling with hyaluronic acid fillers, in patients not willing to undergo surgery, seems to be a viable option for ameliorating the definition of the lower third of the face, although it is mandatory to perform multi-layer injections using fillers with different rheological properties.